PENGARUH ACADEMIC PEER SUPPORT TERHADAP SCHOOL ENGAGEMENT PADA SISWA SMP “X” DI BANDUNG - Theresa Diana Putri Biantoro; Jane Savitri (Provitae: Jurnal Psikologi Pendidikan, 2023)
This study aims to determine the effect of the academic peer support dimension on school engagement at SMP "X" in Bandung. The subjects in this study were the entire population of SMP "X" students with a total of 160 students out of 171 students (there were 4 students who were not willing and 7 students not present. The measuring tool used is Academic Peer Support using the PFASS (Perceived Peer/Friend Academic Support Scale) measuring tool compiled by Jennifer Chen (2005) based on Jennifer Chen`s theory and has been translated by researchers, consisting of 25 items with a reliability of 0.744. The School Engagement measuring tool was developed by Alvin Gultom (2020) based on Friedricks' theory (2004), consisting of 27 items with a reliability of 0.722. This research method uses the effect method which is analyzed by linear regression test using the SPSS 21.0 Version Program. Based on data processing, the results showed that there was a significant influence on the dimensions of academic peer support on school engagement (F = 11,500, R2 = 22.9%; p <0.05), namely interpersonal support (ß= 0.22 , p > 0.05), cognitive support (ß = 0.646, p < 0.05), emotional support (ß = 0.243 , p > 0.05) and instrumental support (ß = 0.243, p > 0.05). Suggestions from researchers are facilitating the occurrence of cognitive support from peers to other fellow students. Cognitive support can be obtained by involving students who excel in groups to support students who have learning difficulties.